2006
DOI: 10.1007/s11095-006-0275-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystal Structure on the Compaction Properties of n-Alkyl 4-Hydroxybenzoate Esters (Parabens)

Abstract: The nanoindentation hardness of the crystals and the tensile strength of directly compressed tablets were each found to correlate directly with the absence or presence of slip planes in the crystal structures of the parabens because slip planes confer greater plasticity. This work presents a molecular insight into the influence of crystal structural features on the tableting performance of molecular crystals in general and of crystalline pharmaceuticals in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 11 publications
8
48
1
2
Order By: Relevance
“…Plastic deformation due to twinning occurs in crystals with low symmetry and few slip systems or when plastic deformation is obstructed due to unfavorable alignment or under high loads. Unlike slip, twinning deformation is homogenous over the entire crystal lattice and is not restricted to multiples of the lattice parameter (45,46,50,58,(92)(93)(94)(95). Compounds with a disordered, corrugated layered structure do not show shearing; they bend or break under applied mechanical stress.…”
Section: Mechanical Properties Of Molecular Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic deformation due to twinning occurs in crystals with low symmetry and few slip systems or when plastic deformation is obstructed due to unfavorable alignment or under high loads. Unlike slip, twinning deformation is homogenous over the entire crystal lattice and is not restricted to multiples of the lattice parameter (45,46,50,58,(92)(93)(94)(95). Compounds with a disordered, corrugated layered structure do not show shearing; they bend or break under applied mechanical stress.…”
Section: Mechanical Properties Of Molecular Crystalsmentioning
confidence: 99%
“…These results were in accord with their structural differences and correlated well with the absence of slip alignment (methyl paraben) or the presence of slip planes (ethyl, propyl, and butyl paraben) in their crystal structures. The increased surface area obtained by plastic deformation in parabens with slip planes caused more interactions between particles and thus the formation of stronger compacts (92).…”
Section: Mechanical Properties Of Molecular Crystalsmentioning
confidence: 99%
“…At the fundamental level, behavior of the material during tablet compression, including capping phenomena, is defined by internal structure of the crystal (8,32,33). At the same time, crystal habit is known to influence compaction profile through its effect on the relative orientation of the crystallites during compression (34,35).…”
Section: Relationship Between the Crystal Morphology And Tabletabilitymentioning
confidence: 99%
“…The deformation behavior of RDX under nanoindentation was revealed by a series of simulations that resembled the experimentally determined deformation behavior of the (100) face. Their study concluded that most of the dislocation loops were found to be parallel to the (001) plane due to the low slip threshold of the (010) [100] active slip system.…”
Section: Cyclotrimethylenetrinitramine (Rdx) Crystalsmentioning
confidence: 99%
“…Nevertheless, such slip activity was absent in anthracene and phenanthrene. The authors attribute this observation to the hindrance to glide along the [100] direction and the availability of a large number of molecules in benzoic acid.…”
Section: Hardness Anisotropy Studies In Some Organic Crystalsmentioning
confidence: 99%